Perancangan Set Area Tunggu Anak Dalam Public Space Mall di Kota Surabaya - Angie Vionata (Intra, 2017)
One of the unmet needs in the mall is the space needed for children to sit and rest. Often children will feel tired walking and need a seat, but can only sit on the edge of the mall shop while waiting for their parents to shop. However, with a special waiting room for children can overcome the problem space. This child waiting area is created with consideration of the child’s activity and space requirements, designed to be attractive and comfortable for the child. Design methods used through several steps, namely formulating problems, literature review and typology, observation, programming, design development, and final design (created prototype 1:1). Set of waiting areas using specific themes of interest to children by providing education based on the theme that carried each set of waiting area. The created formations are taken from the characteristics of each theme, thus giving the impression of a strong theme on each set. Color combinations used dominant pastel colors, which is the color choice of survey results of the most popular community Surabaya.